EFFECT OF TWO ENERGY LEVELS ON THE PRODUCTIVE PERFORMANCE OF GUINEA PIGS (CAVIA PORCELLUS) OF THE PERU BREED - Morales M., Augusto (2011)
The aim of the study was to determine the response in terms of body weight gain,feed intake, feed conversion ratio, and carcass yield in guinea pigs of Peru breed between8 and 12 weeks of age, using two isoproteic diets with different metabolizable energylevels (T1, 2.8; T2, 3.0 Mcal/kg DM) without forage and a third diet (T3) with 2.8 Mcal/kgplus forage. Feed and water were supplied ad libitum. Seventy two male weaned guineapigs (14 ± 3 days of age) were randomly assigned to 24 rearing boxes (8 per treatment).None statistical difference was found between treatments on body weight gain or carcassyield. There was a better feed intake (total dry mater) in T3 (p<0.05). Groups T1 and T2showed a better conversion ratio at week 10 (3.18 and 3.31) than T3 supplied with forage(4.01) (p<0.01).